Synthesis and characterization of rutile titanium dioxide/polyacrylate nanocomposites for applications in ultraviolet light‐shielding materials. Issue 1 (18th February 2014) - Man, Yake; Mu, Luye; Wang, Yun; Lin, Shaohui; Rempel, Garry L.; Pan, Qinmin
<x xml:space="preserve">Abstract</x> Rutile titanium dioxide (TiO2)/poly(methyl methacrylate‐acrylic acid‐butyl acrylate) nanocomposites were synthesized via seeded emulsion polymerization and characterized by Fourier transmission infrared, dynamic light scattering, X‐ray diffraction, ultraviolet–visible (UV–vis) spectroscopy, scanning electron microscopy, transmission electron microscopy, and thermogravimetric analysis to study their UV‐shielding property. The effects of the nanoseed types, surfactant concentrations, and functional monomer amounts on the polymerization conversion, particle size, emulsion stability, and morphologies of the resulting nanocomposites were investigated. The dependence of UV‐shielding performance on the nanoparticle content and dispersion was also explored. The optimized results are obtained with 2 wt% of TiO2 nanoparticles addition, and the effectiveness of UV shielding is significantly increased by using the synthesized rutile nano‐TiO2/polyacrylates, for which the nanocomposite coating with a thickness of 200 μm could block up to 99.99% of UV light (≤350 nm) as confirmed by UV–vis spectrometry. POLYM. COMPOS., 36:8–16, 2015. © 2014 Society of Plastics Engineers